Measuring the Aesthetics of Reading - Larson, Kevin; Hazlett, Richard L.; Chaparro, Barbara S.; Picard, Rosalind W. (2006)
Aesthetic considerations are as important as usability for human-computer interactions, but techniques for measuring aesthetics have been elusive. In this paper, we use the domain of reading to develop new measures of aesthetics. These measures could be applied to any domain. Reading is arguably the most ubiquitous task that people perform on computers. To date, reading research has focused on reader performance, which is typically measured by reading speed and comprehension. But many typographic improvements that make a more beautiful document show little to no measurable difference on traditional performance tasks. We conducted six studies that found two measures that successfully detect aesthetic differences: improved performance on creative cognitive tasks after text is optimized, and reduced activation in the corrugator muscle that is associated with frowning.